THE ROLE OF MARKETING INNOVATION IN CREATING COMPETITIVE ADVANTAGE IN GLOBAL MARKETS - Dewi Indriani Jusuf (Sean Institute, 2022)
This research aims to analyze the role of marketing innovation as a strategic tool capable of creating competitive advantages for companies in the global market. Technological developments and globalization have accelerated changes in the business environment, forcing companies to continuously adapt to these changes in order to remain competitive. This research uses a qualitative approach with literature analysis and case studies to identify marketing innovation practices that are effective in gaining and maintaining competitive advantage in the global market. The research results show that marketing innovation has a crucial role in creating competitive advantages for companies in the global market. Through adopting the right marketing innovations, companies are able to develop unique products or services, respond more effectively to consumer needs, and expand their market share. In addition, marketing innovation also allows companies to build stronger relationships with customers through better experiences and more responsive service. Thus, marketing innovation is recognized as a key element in business growth and success strategies in the modern era full of challenges.